2021
DOI: 10.1080/21655979.2021.1935405
|View full text |Cite
|
Sign up to set email alerts
|

MAPK interacting serine/threonine kinase 1 ( MKNK1 ), one target gene of miR-223-3p, correlates with neutrophils in sepsis based on bioinformatic analysis

Abstract: Sepsis, resulting from a harmful or damaging response to infection, is a complex and severe disease that causes high mortality. Three independent expression profiles of miRNA -GSE94717, GSE149764, and GSE101639 -were collected and integrated to analyze miRNAs associated with sepsis. One miRNA, miR-223-3p, was detected significantly downregulated in patients with sepsis. The upregulated miR-223-3p target genes in patients with sepsis were enriched in central carbon metabolism associated with HIF-1 signaling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, neutrophils promote vascular inflammation and atherosclerosis by delivering miR-155-carrying microvesicles to disease-prone areas ( 139 ). Downregulation of miR-223-3p promotes the expression of mitogen-activated protein kinase (MAPK)-interacting serum/threonine kinase 1 (MKNK 1), which regulates the abundance of neutrophil-expressed inflammatory factors involved in sepsis ( 135 ).…”
Section: Mirnas Regulate Phagocytes In the Pathogenesis Of Chronic Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, neutrophils promote vascular inflammation and atherosclerosis by delivering miR-155-carrying microvesicles to disease-prone areas ( 139 ). Downregulation of miR-223-3p promotes the expression of mitogen-activated protein kinase (MAPK)-interacting serum/threonine kinase 1 (MKNK 1), which regulates the abundance of neutrophil-expressed inflammatory factors involved in sepsis ( 135 ).…”
Section: Mirnas Regulate Phagocytes In the Pathogenesis Of Chronic Di...mentioning
confidence: 99%
“…However, it is not difficult to find from the foregoing that most of the current effects of miRNAs are concentrated in a certain part of a specific disease. For example, miR-223-3p is anti-inflammatory in the context of sepsis ( 135 ) while pro-inflammatory in the context of COPD ( 147 ). We can conclude from this that the effects of miRNAs are environment-specific, that is, the functions of miRNAs on neutrophils and macrophages are highly dependent on surrounding environmental factors, which makes miRNAs have inevitable side effects.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are noncoding RNAs 22–24 nucleotides in length that exist widely in multicellular organisms 11 . MiRNAs modulate gene expression to affect the stability and translation of target mRNAs at the posttranscriptional level 12 . Accumulating studies have revealed the involvement of various miRNAs in AR development 13 .…”
Section: Introductionmentioning
confidence: 99%
“…11 MiRNAs modulate gene expression to affect the stability and translation of target mRNAs at the posttranscriptional level. 12 Accumulating studies have revealed the involvement of various miRNAs in AR development. 13 MiR-31 is downregulated in AR nasal mucosa, and miR-31 upregulation attenuates nasal rubbing, sneezing and IL-13-induced nasal epithelial inflammation during AR pathogenesis.…”
mentioning
confidence: 99%